A method range sidelobes control for a MIMO radar - Võ, Phúc (Journal of Military Science and Technology, 2022)
MIMO radars allow to transmit multiple waveforms from separate sources in space, range-sidelobe performance will be degraded by the cross-correlation between aveforms. This paper presents a new mismatched-filtering approach for designing optimal filters that minimize the integrated sidelobe ratio for MIMO radar.